2021
DOI: 10.1016/j.labeco.2021.101979
|View full text |Cite
|
Sign up to set email alerts
|

Open labor markets and Firms’ substitution between training apprentices and hiring workers

Abstract: Any opinions expressed in this paper are those of the author(s) and not those of IZA. Research published in this series may include views on policy, but IZA takes no institutional policy positions. The IZA research network is committed to the IZA Guiding Principles of Research Integrity. The IZA Institute of Labor Economics is an independent economic research institute that conducts research in labor economics and offers evidence-based policy advice on labor market issues. Supported by the Deutsche Post Founda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…We apply this framework to evaluate the effect of two key European institutions, namely the Schengen Agreement and the Freedom of Movement, on cross-border employment in Europe. While previous literature has studied the labour market effects of these institutions on natives in the host regions (Naguib, 2019;Basten and Siegenthaler, 2019;Aepli and Kuhn, 2019;Åslund and Engdahl, 2019;Beerli et al, 2020), our analysis focuses on sending regions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We apply this framework to evaluate the effect of two key European institutions, namely the Schengen Agreement and the Freedom of Movement, on cross-border employment in Europe. While previous literature has studied the labour market effects of these institutions on natives in the host regions (Naguib, 2019;Basten and Siegenthaler, 2019;Aepli and Kuhn, 2019;Åslund and Engdahl, 2019;Beerli et al, 2020), our analysis focuses on sending regions.…”
Section: Discussionmentioning
confidence: 99%
“…However, studies on the effects of these institutions on cross-border employment of sending regions are scarce. Most of the literature has focused on their effects on migration (e.g., Elsner, 2013;Beine et al, 2019), trade integration (Chen and Novy, 2011;Davis and Gift, 2014;Felbermayr et al, 2018), cross-regional labour market correlations (Bartz and Fuchs-Schündeln, 2012), labour market outcomes of natives in the host regions (Naguib, 2019;Basten and Siegenthaler, 2019;Aepli and Kuhn, 2019;Åslund and Engdahl, 2019;Beerli et al, 2020), and criminality (Sandner and Wassmann, 2018).…”
Section: Related Literaturementioning
confidence: 99%
“…Firms need skilled workers, which they can either train themselves, or recruit from the external labor market (e.g., Aepli and Kuhn 2021). A firm will train, firstly, if the minimal net costs of training are zero or negative, as is the case when the returns from apprentices' productive work are equal to or higher than gross training costs (Mühlemann and Wolter 2014).…”
Section: Curricula and Firms' Training Decisionmentioning
confidence: 99%
“…It is more difficult and more expensive to hire qualified, skilled workers from the external labor market [49]. Therefore, firms can reduce external hiring costs, especially in cases where a high number of workers are needed for a short period (i.e., construction firms), by providing internal training for unskilled workers and then retaining them after they finish training [49][50][51].…”
Section: Hiring Unskilled Craft Workers In the Uae Labour Marketmentioning
confidence: 99%
“…However, many construction industries around the world are witnessing a shortage of skilled workers and face many serious consequences, e.g., poor productivity, safetyrelated incidents, unwanted delays, increased costs, etc. [37,48,51,52]. The availability of research in the context of Singapore also revealed that hiring unskilled workers has posed a serious problem for the industry [56].…”
Section: Hiring Unskilled Craft Workers In the Uae Labour Marketmentioning
confidence: 99%